Quality research needs good working conditions - Rahal, Rima-Maria; Fiedler, Susann; Adetula, Adeyemi; Berntsson, Ronnie P.-A.; Dirnagl, Ulrich; Feld, Gordon Benedikt; Fiebach, Christian J.; Himi, Samsad Afrin; Horner, Aidan J.; Lonsdorf, Tina B.; Schönbrodt, Felix; Silan, Miguel Alejandro A.; et al. (Nature human behaviour, 2023)
High-quality research requires appropriate employment and working conditions for researchers. However, many academic systems rely on short-term employment contracts, biased selection procedures and misaligned incentives, which hinder research quality and progress. We discuss ways to redesign academic systems, emphasizing the role of permanent employment.
Gesehen am 19.02.2024